Optimising Root and Grain Yield Through Variety Selection in Winter Wheat Across a European Climate Gradient - Heinemann, H.; Durand‐Maniclas, F.; Seidel, F.; Ciulla, F.; Bárcena, T. G.; Camenzind, M.; Corrado, S.; Csűrös, Z.; Czakó, Zs; Eylenbosch, D.; Ficke, A.; Flamm, C.; et al. (European journal of soil science, 2025)
ABSTRACT Ensuring food security through sustainable practices while reducing greenhouse gas emissions are key challenges in modern agriculture. Utilising genetic variability within a crop species to identify varieties with higher root biomass carbon (C) could help address these challenges. It is thus crucial to quantify and understand intra‐specific above‐ and belowground performance under varying environmental conditions. The study objectives were to: (a) quantify root biomass and depth distribution in different winter wheat varieties under various pedoclimatic conditions, (b) investigate the influence of variety and pedoclimatic conditions on the relationship between above‐ and belowground biomass production, and (c) assess whether optimised winter wheat variety selection can lead to both greater root biomass C and yield, boosting C accrual. Root biomass, root distribution to 1 m soil depth and root‐to‐shoot ratios were assessed in 10 different winter wheat varieties grown at 11 experimental sites covering a European climatic gradient from Spain to Norway. Median root biomass down to 1 m depth was 1.4 ± 0.7 Mg ha−1. The primary explanatory factor was site, accounting for 60% of the variation in root biomass production, while the genetic diversity between wheat varieties explained 9.5%. Precipitation had a significantly negative effect on total root biomass, especially in subsoil. Significant differences were also observed between varieties in root‐to‐shoot ratios and grain yield. The difference between the variety with the lowest root biomass and the one with the highest across sites was on average 0.9 Mg ha−1 which is an increase of 45%. Pedoclimatic conditions had a greater influence than variety, and determined the relationship's direction between root biomass and grain yield. A site‐specific approach is, therefore, needed to realise the full potential for increased root biomass and yield offered by optimised variety selection.